Reviving the temple of Athena Ilias at Troy/Ilion - Denker, A. (Elsevier Ltd, 2023)
Owing to the legendary fame of Troy's story, the Temple of Athena (the Athenaion) is one of the most enigmatic monuments of antiquity which holds an influential mythical legacy. Long after the great days of Homer's Troy, a new Hellenistic city called Ilion (Roman = Ilium) was founded on the site. At Ilion a new custom that solidified the Homeric credentials of the site was established, and a new temple was built to Athena. Since the temple was almost completely decimated and even its remains were demolished during excavations, it has been one of the most difficult Hellenistic temples to reconstruct. A virtual revival of the non-existing superstructure is presented in this work by synthesizing the existing knowledge (e.g. literary evidence, archaeological evidence, numismatic evidence, topographical evidence, etc.) to support a realistic reconstruction. Along with the immersive visualizations offered by digital technologies, a virtual 3D visit to the sanctuary of the Temple of Athena offers a very attractive opportunity to examine this temple or experience its cultural space. The realistic reconstruction of the Athenaion is important in reviving the Homeric associations of the site and refreshing the memory. © 2023 Elsevier Ltd
Keywords: Ilion; Temple Of Athena; Troy; Virtual 3d Visit; Virtual Reconstruction